Analysis of Social Conflict in Denny Caknan's Satru Song (Study of the Sociology of Literature) - Nurhikmah, Selviana (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
Conflict is a disagreement or difference between two people or groups. Conflict is a part of social life, social conflict is also motivated by differences of opinion brought by individuals in an interaction. Everyone has different characteristics, characteristics and ways of thinking. The existence of differences can make it difficult for people to accommodate themselves, so it can easily trigger some things that lead to conflict. The interests of an individual or group also sometimes clash. Thus, this will lead to conflict between them as well. As in this analysis, this study examines the song popularized by Denny Caknan, namely "Satru 2". With the title song "Satru" which means enemy, but this is not an enemy in ordinary conflicts because the enemy in this case involves a love or romance relationship. In addition, in every lyric and throughout the song, there are misunderstandings between two parties, from small problems to big ones and causing conflict in a relationship. This study uses a qualitative method because the source of the data obtained is obtained on an online website and observations of the behavior of a community. From the results of this study, it is hoped that it will be able to open the public's view that a success in a relationship needs to have equality of opinion so as not to cause social conflict.